2012
DOI: 10.1080/02786826.2011.648780
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Ethanol Fuel Blends on PM Emissions from a Light-Duty GDI Vehicle

Abstract: This study explores the influence of ethanol on particulate matter (PM) emissions from gasoline direct injection (GDI) vehicles, a technology introduced to improve fuel economy and lower CO 2 emissions, but facing challenges to meet next-generation emissions standards. Because PM formation in GDI engines is sensitive to a number of operating parameters, two engine calibrations are examined to gauge the robustness of the results. As the ethanol level in gasoline increases from 0% to 20%, there is possibly a sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
82
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(94 citation statements)
references
References 22 publications
8
82
1
1
Order By: Relevance
“…When the engine is working at the same load, a significant reduction of the PN distribution of the particles can be observed for the ethanol blends equated to gasoline (HE0). The results here are consistent with the PN distribution results reported in previous publications [43][44][45][46][47][48][49]62]. There are many causes leading to a decrease of the PN in the ethanol blends; compared with gasoline fuel, hydrous ethanol and anhydrous ethanol have no aromatic content, a higher laminar flame propagation speed, and a higher percentage of oxygen content.…”
Section: Pm Emission Characteristicssupporting
confidence: 82%
See 1 more Smart Citation
“…When the engine is working at the same load, a significant reduction of the PN distribution of the particles can be observed for the ethanol blends equated to gasoline (HE0). The results here are consistent with the PN distribution results reported in previous publications [43][44][45][46][47][48][49]62]. There are many causes leading to a decrease of the PN in the ethanol blends; compared with gasoline fuel, hydrous ethanol and anhydrous ethanol have no aromatic content, a higher laminar flame propagation speed, and a higher percentage of oxygen content.…”
Section: Pm Emission Characteristicssupporting
confidence: 82%
“…A number of researchers [43][44][45][46][47][48][49] have made a significant reduction in engine-out PM emissions from gasoline engines by using anhydrous ethanol. Price et al [43] reported that anhydrous ethanol blends E85 and E30 showed the lowest PM emissions, followed by methanol blends M85 and M30 for lean fuel-air mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, steady-state EFBC's for the SULEV GDI were substantially larger than for the other LEVs equipped with standard multi-port fuel injection, consistent with previous studies. 28 As expected, EFBC for the diesel vehicle, which was not equipped with a diesel particle filter, was substantially larger than the GDI, ULEV, and LEV vehicles.…”
Section: Constant Velocity (Steady State Operation)mentioning
confidence: 70%
“…However, for GDI engines, the results are divergent [16e19]. For example, some researchers [16,17] have found that adding ethanol to gasoline reduces the GDI engine PM emission. The experiments conducted by Zhang et al [17] were at low speed and high load condition (2000 rpm, 210 Nm), it was found that the E10 and E20 fuels reduced PN emissions from GDI engine.…”
Section: Effects Of Ethanol On Pm Emissions In Gdi Enginesmentioning
confidence: 98%